Case report: Refractory cardiac arrest supported with veno-arterial-venous extracorporeal membrane oxygenation and left-ventricular Impella CP®–Physiological insights and pitfalls of ECMELLA - Thevathasan, Tharusan; Füreder, Lisa; Donker, Dirk W.; Nix, Christoph; Wurster, Thomas H.; Knie, Wulf; Girke, Georg; Al Harbi, Abdulla S.; Landmesser, Ulf; Skurk, Carsten (Frontiers in Cardiovascular Medicine, 2022)
Introduction To the best of our knowledge, this is the first case report which provides insights into patient-specific hemodynamics during veno-arterio-venous-extracorporeal membrane oxygenation (VAV ECMO) combined with a left-ventricular (LV) Impella® micro-axial pump for therapy-refractory cardiac arrest due to acute myocardial infarction, complicated by acute lung injury (ALI). Patient presentation A 54-year-old male patient presented with ST-segment elevation acute coronary syndrome complicated by out-of-hospital cardiac arrest with ventricular fibrillation upon arrival of the emergency medical service. As cardiac arrest was refractory to advanced cardiac life support, the patient was transferred to the Cardiac Arrest Center for immediate initiation of extracorporeal cardiopulmonary resuscitation (ECPR) with peripheral VA ECMO and emergency percutaneous coronary intervention using drug eluting stents in the right coronary artery. Due to LV distension and persistent asystole after coronary revascularization, an Impella® pump was inserted for LV unloading and additional hemodynamic support (i.e., “ECMELLA”). Despite successful unloading by ECMELLA, post-cardiac arrest treatment was further complicated by sudden differential hypoxemia of the upper body. This so called “Harlequin phenomenon” was explained by a new onset of ALI, necessitating escalation of VA ECMO to VAV ECMO, while maintaining Impella® support. Comprehensive monitoring as derived from the Impella® console allowed to illustrate patient-specific hemodynamics of cardiac unloading. Ultimately, the patient recovered and was discharged from the hospital 28 days after admission. 12 months after the index event the patient was enrolled in the ECPR Outpatient Care Program which revealed good recovery of neurologic functions while physical exercise capacities were impaired. Conclusion A combined mechanical circulatory support strategy may successfully be deployed in complex cases of severe cardio-circulatory and respiratory failure as occasionally encountered in clinical practice. While appreciating potential clinical benefits, it seems of utmost importance to closely monitor the physiological effects and related complications of such a multimodal approach to reach the most favorable outcome as illustrated in this case.